(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The intellectual and spiritual legacy of Najm al-Din Kubra (1145-1221) is commonly examined within the history of Sufism, while its educational structure has received less systematic pedagogical interpretation. This study analyzes the Kubrawiyya school as a historical model of guided personal development and identifies conceptual parallels between its practices and selected principles of contemporary education. A qualitative, document-based historical-comparative design was employed. The source corpus included Kubra’s principal doctrinal framework, classical accounts of the Kubrawi tradition, modern scholarship on the order, and educational literature on mentoring, scaffolding, reflection, mindfulness, staged competence, and whole-person learning. The materials were coded according to educational purpose, the role of the guide, the position of the learner, instructional processes, developmental stages, assessment, and social responsibility. The findings reveal five interconnected pedagogical features: individualized guidance through the murshid-murid relationship; conscious and disciplined practice associated with sobriety; progressive development from initiation to stability; self-observation and reflective regulation; and the integration of personal formation with ethical and civic responsibility. These features resemble, but should not be equated with, modern mentoring, scaffolding, reflective learning, and holistic education. The Kubrawiyya tradition therefore offers a historically grounded conceptual resource for culturally responsive pedagogy. Its contemporary use requires critical adaptation, voluntary participation, ethical safeguards, and a clear distinction between spiritual authority and professional educational roles